3D printable Sodium alginate-Matrigel (SA-MA) hydrogel facilitated ectomesenchymal stem cells (EMSCs) neuron differentiation. (January 2021) - Li, Yang; Cao, Xia; Deng, Wenwen; Yu, Qingtong; Sun, Congyong; Ma, Ping; Shao, Fengxia; Yusif, Mukhtar Mohammed; Ge, Zhumei; Wang, Kaili; Li, Ran; Yu, Jiangnan; et al.
Ectomesenchymal stem cells (EMSCs) are typical adult stem cells obtained from the cranial neural crest. They have the potential to differentiate into various cell types, such as osseous cells, neurons and glial cells. Three-dimensional (3 D) printing is a novel method to construct biological structures by rapid prototyping. Previously, our group reported on the stemness and multi-lineage differentiation potential of EMSCs on gels. However, the exploration of EMSCs in 3 D printing and then evaluation of the growth and neuronal differentiation of EMSCs on extruded 3 D printable hybrid hydrogels has not been reported. Therefore, the current study explored the novel hybrid Sodium alginate-Matrigel (SA-MA) hydrogel extruded 3 D printing to design an in vitro scaffold to promote the differentiation and growth of EMSCs. In addition, the physical properties of the hydrogel were characterized and its drug-releasing property determined. Notably, the results showed that the construct exhibited a sustain-released effect of growth factor BDNF in accordance with the Higuchi equation. Moreover, the cell survival rate on the 3 D printed scaffold was 88.22 ± 1.13% with higher neuronal differentiation efficiency compared with 2 D culture. Thus, SA-MA's ability to enhanced EMSCs neuronal differentiation offers a new biomaterial for neurons regeneration in the treatment of spinal cord injury.